Stimulasi Kemampuan Motorik Halus Anak Melalui Modifikasi Kegiatan Mengancing dan Mengikat - Juliana Juliana; Rahmah Rahmah; Swandra Rahayu (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
This study aims to improve the fine motor skills of children aged 5-6 years at TK Negeri Bantar through 2M activities (buttoning and tying). The main problem in this research was the low hand-eye coordination of children, where in the initial condition, the "Not Yet Developed" (BB) category reached 60%. The method used was Classroom Action Research (CAR) conducted in two cycles, each consisting of two meetings. The subjects of the study were Group B children at TK Negeri Bantar. Data collection techniques were carried out through observation and documentation. The results showed that in Cycle I, children's fine motor skills began to improve but were not optimal, with the average "Developed as Expected" (BSH) category at 30%. After improving the actions in Cycle II through media modification and intensive assistance (scaffolding), children's fine motor skills increased drastically to 90% in the BSH category, and the BB category decreased to 0%. A significant increase occurred from Cycle I to Cycle II by 60%. The conclusion of this study is that 2M activities are effective in significantly improving early childhood fine motor skills.